Analisis Penerapan Upah dalam Upaya Meningkatkan Kinerja Karyawan Pabrik Roti Jarwan Sangatta - Riski, Meita Sondang; Azizi, M. Paris (Politeknik Negeri Samarinda, 2024)
The aim of this research is to analyze the application of wages in an effort to improve the performance of Jarwan Sangatta bakery employees. Research analysis uses descriptive qualitative, namely in the form of a series of information extracted from research results but still in the form of verbal facts, or still in the form of statements made during preparation before entering the field, during the field and after completion in the field. Data collection techniques are carried out by conducting observations, interviews and documentation. Interviews were conducted with 5 (five) informants, namely: the owner of the bakery, the finance department, the head of production, the canvas department and the cook. The analytical tool used in this research is miles and huberman, namely by carrying out reduction, display and conclusion methods. The research results show that employees of the Jarwan Sangatta bakery do not yet have a work agreement between the employees and the owner of the Jarwan Sangatta bakery, related to wages. Apart from that, employees also do not have labor social security.